Effects of PEEP on respiratory mechanics and arterial oxygenation during prone positioning [Pron pozisyonda PEEP uygulamasi{dotless}ni{dotless}n solunum mekaniǧi ve arteriyel oksijenizasyon üzerine etkileri] - (:unkn) unknown (My University, 2013)
Objectives: To evaluate the changes in arterial oxygenation and vital parameters by applying 10cm H2O positive end-expiratory pressure (PEEP) to patients undergoing lumbar spine surgery in the prone position. Patients and Method: According to The American Society of Anesthesiologists (ASA) status I-II, 40 patients, scheduled for lumbar discectomy in the prone position were enrolled in the study. During the anesthesia induction and after intubation they were ventilated with intermittent positive pressure ventilation (IPPV) mode, 60%N2O-40%O2, 4L.min-1 flow and 0.7-1.0 minumum alveolar concentration (MAC) sevofurane. The patients were randomized into 2 groups. PEEP value was set at 0 cm H2O in PEEP 0 group and at 10 cm H2O in PEEP 10 group. Respiratory rate 10/min, inspiration-expiration ratio 1:2 and tidal volume 8ml.kg-1 were kept constant. Blood gas samples were obtained 10 min after induction and 15-30-45-60-75-90 min after prone positioning. Vital parameters, dynamic compliance and side effects were recorded. Results: Mean blood pressure was statistically low in PEEP 10 group at the prone positioning, compared to the other periods (p<0.05). Pulse rate in both groups was significantly low during the prone period compared to other periods (p<0.05). PaO2 and compliance were statistically high in PEEP10 group at the prone position as compared to the PEEP 0 group (p<0.05). Conclusion: In our opinion, applying 10 cm H2O PEEP to patients undergoing spine surgery in the prone position is a beneficial implementation.
Keywords: Oxygenation; PEEP; Peroperative ventilation; Prone positioning; Respiratory mechanics